Therapy-induced E-cadherin downregulation alters expression of programmed death ligand-1 in lung cancer cells. (July 2017) - Suda, Kenichi; Rozeboom, Leslie; Rivard, Christopher J.; Yu, Hui; Ellison, Kim; Melnick, Mary Ann C.; Hinz, Trista K.; Chan, Daniel; Heasley, Lynn E.; Politi, Katerina; Mitsudomi, Tetsuya; Hirsch, Fred R.
Highlights: PD-L1 was decreased after acquisition of resistance to TKIs in multiple cell lines. Decreased PD-L1 expression was observed in cells with E-cadherin downregulation. ShRNA-mediated E-cadherin knockdown decreased PD-L1 expression. Chemotherapy-induced E-cadherin downregulation also decreased PD-L1 expression. Abstract: Objectives: Immunotherapy that targets the programmed death-1/programmed death-ligand 1 (PD-L1) axis has been approved for treatment of non-small cell lung cancer (NSCLC) patients in many countries. However, our current understanding of the role of immunotherapies on NSCLC patients with epidermal growth factor receptor ( EGFR ) mutation, following acquisition of resistance to EGFR tyrosine kinase inhibitors (TKIs), is so far unclear. Especially, there is little data on if each acquired resistance mechanism to EGFR-TKIs alters PD-L1 expression status which is employed as an important predictive biomarker for PD-1/PD-L1 targeting agents. Materials and methods: Lung cancer cell lines (HCC827, HCC4006, PC9, H1975, H358, SW900, and H647) and their daughter cells that acquired resistance to EGFR-TKIs or cytotoxic drugs (cisplatin or vinorelbine) were examined. PD-L1 expression was analyzed by immunohistochemistry, immunoblotting, and/or fluorescent imaging. Published microarray data were also employed to evaluate our findings. Results and conclusion: We found correlations between therapy-induced E-cadherin downregulation and decreased PD-L1 expression using our cell lines and published microarray data. ShRNA mediated E-cadherin knockdown decreased PD-L1 expression in parental cells, and dual immunofluorescent staining of E-cadherin and PD-L1 suggests co-localization of both molecules. We also observed marked downregulation of PD-L1 in cells with E-cadherin downregulation after chronic treatment with vinorelbine. These results indicate a correlation between therapy-induced E-cadherin downregulation and decreased PD-L1 expression, highlighting the importance of re-biopsy after acquisition of resistance to EGFR-TKIs, not only for the evaluation of resistance mechanisms but also for the determination of PD-L1 expression status.